ANALISIS PENDAPATAN PETANI DAN KEUNTUNGAN USAHATANI CABAI MERAH KERITING DI DESA SINDULANG, KECAMATAN CIMANGGUNG, KABUPATEN SUMEDANG - Amalia, Rizky; Qanti, Sara Ratna; Suminartika, Eti; Saidah, Zumi (Jurnal Agristan, 2024)
The price of chilies in West Java has still fluctuated over the last 12 months. Penyangga Aneka Cabai program is considered to be a solution for farmers to increase their income so that farmers have enough capital to carry out chili production and can play a role in maintaining price stability and chili supply. One of the villages used as an area for Penyangga Aneka Cabai is Sindulang Village in Cimanggung District, Sumedang Regency with the main commodity being red chilies. This research aims to analyze the comparison of farmers' income and profits from red chili farming that participate in Penyangga Aneka Cabai program with those that do not participate in Penyangga Aneka Cabai program. This research uses a quantitative approach design, survey method and has a sample size of 67 red chili farmers with appropriate criteria. Data analysis techniques are carried out using descriptive analysis, farming analysis, R/C Ratio analysis, and Kruskal-Wallis and Mann-Whitney statistical test. The research results show that the average income of program farmers is IDR 35,330,175/ha/planting season which is greater than the income of non-program farmers of IDR 30,564,982/ha/planting season. Average R/C value Ratio program farmers is 2.64 which is also greater than non-program farmers, namely 2.03. This research proves that farming carried out by farmers who take part in Penyangga Aneka Cabai Program is more profitable. However, farming carried out by program and non-program farmers is feasible and efficient to operate because both have an R/C value of more than 1. Keywords: Red Chilies, Penyangga Aneka Cabai, Planting Patterns, Intercropping